Nature and Skills of Effective Leadership for The Success of Literacy Programs in Elementary Schools - Wibowo, Udik Budi; Sayekti, Octavian Muning; Dewanti, Septinda Rima (Jurnal Prima Edukasia, 2023)
The School Literacy Movement program launched by the government has not yet been to be implemented optimally. One of the factors that influence it is related to the leader"”in this case, the principal. Therefore, this study aims to identifying the traits and skills of effective leadership in the success of literacy programs in schools. This research employed a qualitative case study research. Questionnaires and interviews were done to collect data. Respondents of this study were teachers who were members of the professional education program in positions at Yogyakarta State University in 2023. This study employed interactive analysis techniques for its data analysis. This study shows that the traits and skills of effective leadership for the success of literacy programs in elementary schools are personality, motivation, and skills, respectively.